RADIATION DOSE ESTIMATION WITH CALDOSE_X VERSION 5.0 IN RADIOLOGICAL LABORATORY DEPARTMENT OF RADIODIAGNOSTIC AND RADIOTHERAPY TECHNIQUE - Agung Nugroho Setiawan (Jurnal Imejing Diagnostik (JImeD), 2019)
Background: Media in the educational perspective is a strategic instrument in determining the success of the teaching and learning process. On radiographic examination, each patient is always at risk of exposure to ionizing radiation that is not necessary. Students need to learn whether the exposure factors which they use on patients is still below of the diagnostic reference level. This article purpose to get an overview of the radiation dose estimation using CALDose_X version 5.0 software as a laboratory-learning instrument in Radiological Laboratory Department of Radio diagnostic and Radiotherapy Technique, Poltekkes Kemenkes Semarang.Methods: This article contains a description of using this software. The sample type is purposive sampling, which consist of seven types of radiographic examinations belong to The Head of Bapeten Regulation Number 8 of 2011. Entrance surface air kerma (ESAK) value from each exposure factors compared with Bapeten dose limit.Results: The result showed this software able to calculate the incident air kerma of radiographic examination based on the output parameters of an X-ray tube. All of ESAK values confirm with the Bapeten dose limit.Conclusion: The CALDose_X version 5.0 can be proposed as an instructional media to teach students in estimating absorbed dose to organs and tissues of the human body, the effective dose as well as the patient’s cancer risk for radiographic examinations.